Christmas at Carnton [large type] - Alexander, Tamera (Center Point Large Print, 2017)
"Amid war and the fading dream of the Confederacy, a wounded soldier and a destitute widow discover the true meaning of Christmas--and of sacrificial love. Set against the backdrop and history of the Carnton Plantation in Franklin, Tennessee."--